Diffusion Tensor Imaging and Fiber Tractography in Parry-Romberg Syndrome - Moon, W.J.; Kim, H.J.; Roh, H.G.; Oh, J.; Han, S.H. (American Journal of Neuroradiology, 2008)
SUMMARY: We report a case of Parry-Romberg syndrome in a 32-year-old woman presenting with intermittent headache and mild sensory disturbance. MR imaging revealed minimal asymmetric atrophy of the right hemisphere with a few nonspecific white matter hyperintensities. Diffusion tensor imaging and fiber tractography, however, demonstrated clear fiber derangement, especially in the sensory tract of the right cerebral white matter.